Underground Space for Infrastructure Development and Engineering Geological Challenges in Tunneling in the Himalayas - Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
Being topographically steep and consisting of many rivers originating from the glaciers of the Himalaya, Nepal is gifted in water resources. As a developing country, Nepal needs to accelerate to develop its crucial infrastructures for the economic prosperity of the nation. This is achievable by developing the enormous hydropower potential available, making short and efficient roads through the steep mountain topography, extracting mines for various purposes, and providing cost effective solutions for the storage facilities. These developments are not possible unless tunnels and underground caverns are used. Due to tectonic activity, however, the rock mass in Nepal and across the Himalayan region is somewhat different in their engineering behaviour. These differences in mechanical behaviour are mainly caused by a high degree of folding, faulting, shearing, fracturing and deep weathering. As a result, severe instability problems associated with this complex geological setup have to be faced during tunnelling. This is the major challenge to be addressed in a scientific manner in order to make tunnel option more cost effective, feasible and safer. This paper delineates the possible areas where tunnels and underground caverns are needed and may play an important role in the socio-economic development of the nation, discusses the major geological challenges faced while tunnelling, and briefly describes methodologies to be used for analysing geological uncertainties. Key words: Himalayan geology, tunnelling, Nepal Hydro Nepal: Journal of Water, Energy and Environment Vol. I, Issue No. 1 (2007) pp. 43-49